Unmet need for contraception among married adolescent girls and young women in Haramaya Health and demographic surveillance system, Eastern Ethiopia - Hailu, Saba; Assefa, Nega; Dingeta, Tariku; Abdurahman, Chaltu; Adem, Mewardi (Frontiers in Global Women's Health, 2022)
Background – Unmet need for contraception is highest in low and middle income countries. Contraceptive use among young women, whether married or unmarried, is lower than older women in the developing world. Previous studies done generalized the finding for all reproductive aged women and also didn’t investigate psycho-social factors affecting contraceptive use. This study aimed at identifying factors associated with unmet need for contraception among young married women in Haramaya HDSS, East Ethiopia. Methodology: A community-based cross sectional study was employed among young married women aged 15–24 years. A simple random sampling method was used to select 550 young married women. Data was collected using a pretested structured questionnaire. Adjusted Odds Ratio (AOR) with 95% Confidence Intervals (CI) was used to identify factors associated with unmet need for contraception using multivariable logistic regression analysis. Result: The overall prevalence of unmet need for contraception was 154(30.3%). Adolescents (15-19) (AOR=2.05, 95% CI: 1.16- 3.62), Husbands negative attitude towards contraception (AOR=2.1, 95% CI: 1.05-4.46), Never use of contraception (AOR= 3.9, 95% CI: 2.29 - 6.71) were significantly and positively associated with unmet need for contraception. On the other hand young women with secondary or above educational status (AOR=0.55, 95% CI: 0.28 -1.084) were negatively and significantly associated with unmet need for contraception. Conclusion- The prevalence of unmet need for contraception among young women in Hararmaya was high. Unmet need was affected by age, husband’s attitude towards contraceptive, educational status of women, and previous use of contraception. The study underscored the need to improve girls' educational status to empower them regarding decision-making on contraceptive use with their partners. Programs should also engage male partners since they are perceived as a key in decision-makers when it comes to contraceptive use.